The purpose of playing : Shakespeare and the cultural politics of the Elizabethan theatre - Montrose, Louis (The University of Chicago Press, 1996)
Part of a larger project to examine the Elizabethan politics of representation, Louis Montrose's The Purpose of Playing refigures the social and cultural context within which Elizabethan drama was created.